Improving performance of Virtual Machines by Virtio bridge Bypass for PCI devices (International Journal of Engineering and Computer Science, 2017)
Inspired by the Virtio module of virtualization, we propose an alternate method to directly communicate with PCI devices such as NIC without the use of any kernel modules. This method uses a specialized module written by us which will avoid the mechanism of bridges like the ones used in Virtio that increase latency. This module will be present in the userspace of the guest OS and we are specifically targeting the e1000 device for this purpose and later plan to make it generic for all PCI devices. Our motivation is to avoid unnecessary communication with the kernel which slows down the system. For the first step. we do resource mapping to map the PCI device memory into userspace. Then, we expose PCI configuration space through a userspace module using ACPI cables. Thus, we create a userspace PCI driver which will decrease the latency in access time and increase speed of execution. The applications in the Guest OS that request communication with the PCI devices will be redirected to our application. This will take some load off the kernel and reduce its overhead. Finally, we boot a VM that actually talks to our PCI device emulator.